Implementation of Communipreneur Concept In Development Campus Entreprenial - H. Muchsin al-Fikri; Tresia Wulandari; Nur Aeni Karimah (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2021)
This study aims to internalize the concept of communipreneur socialized by the Faculty of Social and Political Sciences, Sangga Buana University, Bandung and examine the implementation of the communipreneur concept on the campus. Through a qualitative method approach, researchers conducted observations and dept-interviews with key informants namely the Vice Dean, Witri Cahyati, S. Sos, M.Si, Chairperson of the Department of Communication Science, Pupi Indriati Zaelani, S. Sos, M. Si and several USB lecturers. This study produced several conclusions including; Sangga Buana University as a campus that claims to be an entrepreneur campus is required to make maximum efforts to apply the concept of entrepreneurs to support the birth of students who are independent and entrepreneurial in the field of Communication. The rector’s policy was further broken down by the Communication Study Program at the Faculty of Social and Political Sciences by formulating and implementing the concept of communi-entrepreneur through four fields namely photography, videography, public speaking and script writers. Penelitian ini bertujuan untuk menginternalisasi konsep komunipreneur yang disosialisasikan oleh Fakultas Ilmu Sosial dan Politik Universitas Sangga Buana Bandung dan meneliti implementasi konsep komunipreneur di kampus tersebut. Melalui pendekatan metode kualitatif, peneliti melakukan observasi dan dept-interview kepada key informan yaitu Wakil Dekan, Witri Cahyati, S. Sos, M. Si, Ketua Jurusan Ilkom, Pupi Indriati Zaelani, S. Sos, M. Si dan beberapa dosen USB. Penelitian ini menghasilkan beberapa kesimpulan diantaranya; Universitas Sangga Buana sebagai kampus yang mengklaim sebagai kampus entrepreneur dituntut berupaya secara maksimal untuk menerapkan konsep enterpreneur guna mendukung terlahirnya para mahasiswa yang berjiwa mandiri dan berwirausaha di bidang Komunikasi. Kebijakan rektorat tersebut selanjutnya dibreakdown oleh Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik (Fisip) dengan merumuskan dan mengimplementasikan konsep komunipreneur melalui empat bidang yaitu fotografi, videografi, publik speaking dan script wraiter.